ASPEK HUKUM DAN PENYELESAIAN ATAS TRANSAKSI PEMBAYARAN JUAL BELI MENGGUNAKAN KARTU ELEKTRONIK - Tina Marlina; Ismayana Ismayana; Dudung Hidayat (Fakultas Hukum Universitas 17 Agustus (UNTAG) Semarang, 2021)
This study aims to analyze the legal aspects of the use of credit cards as a meansof payment and settlement efforts from the bank in the event of a customer who does not pay the credit card. This research is a juridical-normative research, with the approach used, namely the statutory regulation approach and legal norms in accordance with existing legal issues related to the structure and principles of the applicable law. The results of the first research are that the legal aspects related to the use of credit cards in Indonesia include various regulations such as Law Number 19 of 2016 to Bank Indonesia Regulations, namely Bank Indonesia Regulation Number 14/2/PBI/2012 concerning Amendments to Bank Indonesia Regulation Number 11/11/PBI/2009 concerning the Implementation of Card-Based Payment Instrument Activities. Second, there are several attempts made by the bankingsector in solving problems when there is default by the customer, these efforts can be carried out by conducting Negotiation, Mediation, Conciliation, Arbitration and Judiciary. With the existence of several alternatives in solving the problem, the bank can choose the efforts to be taken, such as the Cirebon Branch of Bank Rakyat Indonesia which chose mediation as the solution to the problem. Mediation is the main solution carried out at BRI Cirebon Branch, it is more effective and efficient in solving the problem, mediation as an effort to solve problems also has a strong legal basis and legitimacy as stipulated in Bank Indonesia Regulation Number 8/5/PBI/2006 concerning Banking Mediation.